Profesionalisme Akuntan Pendidik : Perspektif Atau Triger Kualitas Lulusan Akuntansi Di Era Masyarakat Ekonomi Asean - Heri Prasetyo; Abdul Wahid Mahsuni; Junaidi Junaidi (Universitas Islam Malang, 2017)
ABSTRACT The research examines the effect competences, professional commitment of accountant educators toward The quality of graduates in accounting in facing Asean Economic Community. This research use sample consisted of 6 universities in Malang. The data are taken with method of collecting data into questionnaires central. Selection of samples by using purposive sampling. The result of the research indicated, Competences, Professional Commitment of Accountant educators are factors that affect positively on The quality of graduates in Accounting. The positive result gives contribution that improving the quality of human resources, competence and professional commitment educators accountant is a necessary condition for achieving the level of success in the future. These findings contribute that improving the quality of accounting graduates through professional commitment strategies of educators accountants such as being independent, enhancement training and conferences, work teamwork and improving the competence that relevant with orientation of the accounting department and be able to evaluate objectively learning will realize the Indonesian people who are ready to face the regional and global economy as AFTA (Asean Free Trade Area), APEC(Asia Pacific Economic Community), GATT (General Agreement on Tariffs and Trade)/ WTO (World Trade Organization), and to meet the ASEAN Community 2015.Keywords : the quality of graduates in accounting, competences, professional commitment, accountant, educators